Factors influence self-care behavior and diabetic management in patients with diabetes mellitus - Ni Luh Putu Sekardiani; I Ketut Swarjana; Ni Luh Adi Satriani; Sri Dewi Megayanti (Medisains, 2023)
Background: Self-care behavior and diabetic management in patients with diabetes mellitus (DM) tends to be low, especially during the COVID-19 pandemic. Various studies have found the influence of knowledge with self-care behavior diabetic management, as well as attitudes, motivation, family support and self-efficacy, but research analyzing the most dominant factors that play a role in influencing diabetic patients in self-care behavior and diabetic management is still limited.